(untitled) (Indian Journal of Chemical Technology (IJCT), 2023)
Numerous scientific and technological developments in wastewater treatment procedures are brought on by the shortage of clean water supplies. Heavy metals’ recalcitrance in wastewater has been shown to be a difficult issue. Further, drinking water quality must be at its highest for human health to be at its best; nevertheless, a number of human activities are continuously degrading it, which has an effect on human health either directly or indirectly. Because heavy metals are the primary causes of many chronic illnesses and have a tendency to bio accumulate, they are giving rise to a lot of worries. Technologies from all over the world are being developed to address the demand for clean drinking water. The objective of the current study is to raise awareness of the need to remove dangerous dense metals from various types of wastewater and the application of modified graphene nanocomposite for their adsorption-based removal. Graphene-based nanocomposite materials have been picked for this application due to their large surface area, superior mechanical strength, and reactivity towards polar and nonpolar contaminants for the electrostatic emission of the heavy metal ions arsenic (As), chromium (Cr), copper (Cu), and lead (Pb).